Evaluation of herbal ointment formulated with Wrightia tinctoria (ROXB) R. BR. leaves for efficacy of wound healing. - T senthil kumar; D. Venkappayya; Vilambi N.R.K. Reddy; R. Manavalan (International Journal of Phytomedicine, 2013)
The objective in wound management is to heal the wound in the shortest time possible, without infection and fast wound closure. This investigation is to check the rationale behind the traditional use of leaves of Wrightia tinctoria by evaluating the wound healing property of formulated ointment containing Wrightia tinctoria which may facilitate in vivo quantification of skin curative property of the ointment. Controlled wound healing efficacy studies were done on Guinea pig model with incision and excision wounds. Suitable ointment base was selected by Preformulation studies. The ointment was prepared by melt pour and mixing technique with incorporation of Wrightia tinctoria extract in coconut oil. The wound healing effects of the formulations were compared to that of 0.2% w/w nitrofurazone ointment. A better healing pattern with complete wound closure was observed with the treated groups in contrast to the control group. The total epithelization period was 14 days (allopathic control and Wrightia tinctoria ointment) with 19 days for ointment base. The wound contraction to 50% took 6.3 days (allopathic control), 6.5 days (Wrightia tinctoria ointment), against 12.7 days for ointment base. The tensile strength of the test was almost the same as standard ointment. Increased wound breaking strength indicates increase in collagen strength and obviously facilitating wound healing, thus proving that Wrightia tinctoria ointment could be used for wound healing as a safe alternative to synthetic drug ointments.